The Effect Of Woolwich Massage Therapy On The Flowness Of Breast Milk In Public Mothers At The Bulu Tuban Community Health Center - Qiftiyah, Mariyatul; Umu Qonitun (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Background: : Failure to breastfeed can cause several problems during the postpartum period. Breast care has an important role in this matter, one of which is by carrying out Woolwich massage on postpartum mothers. This study aims to find out whether Woolwich massage therapy has an effect on the smoothness of breastfeeding in postpartum mothers at the Bulu Community Health Cente Tuban Regency. Method: The research was conducted in July 2024 at the Bulu Tuban Community Health Center. The methodology used is quasy experiment. The independent variable is Woolwich massage while the dependent variable is smooth breastfeeding. The sample size was 16 respondents using a simple random sampling technique. Data processing uses the Wilcoxon Signed Rank test with a significance level of ρ < α (0.05).Result: All postpartum mothers experienced that their breast milk was not flowing smoothly before Woolwich massage therapy was carried out, all postpartum mothers experienced smooth milk production after Woolwich massage therapy. After carrying out statistical tests, it was found that the ρ-value was 0.000, so the ρ-value <0.05 so that H₀ was rejected. This proves that there is an influence of Woolwich massage therapy on the smooth flow of breast milk in postpartum mothers at the Bulu Community Health Center Tuban Regency. Conclusion : The results of this study can provide input and information about the effect of Woolwich massage therapy on the smooth flow of breastfeeding in postpartum mothers so that health workers can optimize their provision of midwifery care to postpartum mothers